The institutional wife syndrome: A metaphor grounded in reality - Barbara A. Mccaulay; Virginia G. Gonzalez (Adult Education Research Conference, 1993)
The metaphor, institutional wife syndrome, provided a basis on which to examine women's experience in higher education administration. Subsequent research was conducted to examine the effect of this metaphor in transforming perspective.